Wireless-Powered Full-Duplex UAV Relay Networks over FTR Channels - De Paiva Mucin, Daniel [UNESP]; Osorio, Diana Pamela Moya; Olivo, Edgar Eduardo Benitez [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
A thorough understanding of fundamental limits of wireless-powered unmanned aerial vehicle (UAV) relay networks in millimeter waves is still missing. We narrow this gap by investigating the outage performance of a UAV-assisted wireless network over fluctuating two-ray (FTR) channels. The FTR fading model is particularly appealing since well characterizes the wireless propagation in a wide range of frequencies, including those in millimeter waves. The proposed setup consists of a source-destination pair communicating with the assistance of a UAV, which is a wireless-powered relay station operating in full-duplex mode under the amplify-and-forward protocol. For the wireless energy harvesting at the UAV, wireless power transfer (WPT), simultaneous wireless information and power transfer (SWIPT), and self-recycling energy techniques are employed together. To characterize the system outage probability, we obtain an integral-form expression derived from an approximate analysis and a simple closed-form expression derived from an asymptotic analysis at the high signal-to-noise ratio (SNR) regime. Monte Carlo simulations are provided to validate the correctness of our theoretical results and provide insights on the network performance in terms of key system parameters. Interestingly, obtained results show that the FTR fading parameters corresponding to the first hop and second hop play no role on the system outage performance at high SNR. Instead, it is mainly governed by the effect of the residual self-interference at the UAV, leading to outage floors.
Keywords: Fluctuating two-ray; full duplex; mmWave communications; outage probability; simultaneous wireless information and power transfer; unmanned aerial vehicle